2015
DOI: 10.1111/j.1728-4465.2015.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influences on Sexual Activity among Adolescents in Ghana

Abstract: Little is known about the influences of peers on the sexual activity of adolescents in sub-Saharan Africa. Better understanding of these issues could lead to more effective interventions promoting sexual and reproductive health. Using two waves survey data from adolescents (n=1275) in two towns in southeastern Ghana, we examined age, gender, and community differences in peer group characteristics. We also examine prospective associations between peer group characteristics and self-reported sexual initiation, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 91 publications
6
35
1
1
Order By: Relevance
“…This study identified peer pressure as an important predictor of risky sexual practice. This finding is in line with a study in Ghana and a meta-analysis conducted in sub-Saharan Africa [ 38 , 39 ]. The reason for this may be that people do not want to be different or rejected, and they may engage in risky behaviors because of the pressure from friends; this may especially be true for youth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study identified peer pressure as an important predictor of risky sexual practice. This finding is in line with a study in Ghana and a meta-analysis conducted in sub-Saharan Africa [ 38 , 39 ]. The reason for this may be that people do not want to be different or rejected, and they may engage in risky behaviors because of the pressure from friends; this may especially be true for youth.…”
Section: Discussionsupporting
confidence: 92%
“…The Global School-Based Student Health Survey (GSHS) conducted in Trinidad and Tobago showed that men were more likely to engage in premarital and early sex than women [ 33 ]. A large-scale study conducted by Mid-western State University reported that men were more likely to engage in risky sexual practice compared to women [ 39 ]. Men are also more likely to have multiple sexual partners compared to women [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Friends played an important role in influencing adolescents to engage in pre‐coital and sexual behaviors. These findings support previous studies in Thailand that showed that perceived peer norms influenced sexual risk behaviors (Srijaiwong et al, ; Tipwareerom et al, ), the importance of friends in influencing the decision to engage in sexual intercourse (Bingenheimer et al, ), and the role of friends in unintended recurrent pregnancies among adolescents (Aeamsamarng, Srisuriyawet, & Homsin, ). However, among adolescents who had a boyfriend/girlfriend, partner approval of sex was the most significant factor influencing pre‐coital and sexual behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…Within the family context, parent–adolescent communication (Harris et al, ), parental monitoring (Rhucharoenpornpanich et al, ), and parental disapproval of sex (Atwood et al, ) prevented sexual risk behaviors, while authoritarian parenting style increased risky sexual behaviors among adolescents (Schuster, Mermelstein, & Wakschlag, ). In adolescence, peers play a crucial part in shaping adolescents' attitudes toward sex and sexual risk behaviors, and perceived peer norms toward sexual behaviors were a strong predictor of sexual behavior intent (Chen, Neilands, Chan, & Lightfoot, ) and engaging in sexual risk behaviors (Bingenheimer, Asante, & Ahiadeke, ). Partner approval of sex was found to be positively associated with sexual initiation among adolescents (Villarruel, Jemmott III, Jemmott, & Ronis, ), and openly discussing sexual health with partners was associated with more frequent condom use among sexually‐active adolescents (Widman, Choukas‐Bradley, Helms, Golin, & Prinstein, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation